Assessing the livelihood of slum dwellers in Dhaka city (Journal of the Bangladesh Agricultural University, 2010)
The present study was an attempt to determine the factors affecting the livelihood of the socioeconomic improvement of migrants and to analyze the causes of rural-urban migration in slum areas. Slum areas have no available formal education facilities and slum people were found to be engaged in rickshaw pulling, day labourer, petty business, small job services etc. Analysis showed that migration and taking in micro credit were beneficial for the slum dwellers. Receiving and utilizing micro credit income level, consumption, expenditure and socio-economic status of the slum dwellers improved to some extent. Due to participation of slum dwellers in NGOs, their economic, social and decision making improved substantially. Credit disbursement through NGOs with integrated approach could bring positive changes in the life of poor slum women as well as their community. Findings showed that Fifty six per cent people migrated to Dhaka city for economic reason. Factors of migration had a significant contribution of rural urban migration and also significant livelihood improvement has taken place due to micro credit. At the individual level, the women were benefited in terms of mobility and skill, self confidence, widening of interests, access to financial services, build own savings, competence in public affairs and status at home and in the community that lead a better awareness for enhancing women's empowerment. However, there is a need for proper training for sustainable result in the long run. Keywords: Migration; Livelihood; Micro credit DOI: 10.3329/jbau.v7i2.4750 J. Bangladesh Agril. Univ. 7(2): 373-380, 2009